2011
DOI: 10.1007/s11250-011-9804-6
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on using autologous and heterologous boar sperm supernatant from freezing processes as post-thawing solution: its effect on sperm motility

Abstract: The aim of this study was to evaluate the effect of post-thawing dilution with autologous and heterologous sperm supernatant on motility of frozen-thawed boar spermatozoa. During the cryopreservation, sperm supernatant (a combination of seminal plasma and semen extender, 50% v/v) or seminal plasma from nine boars (Duroc, Large White, and Landrace; three in each) was collected by centrifugation and stored frozen until use as post-thawing solution. Sperm pellets were further processed and cryopreserved using con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…In the present study, we found that treatment with either autologous or homologous SP resulted in higher viability rates as compared with control and, no detrimental effects when using the homologous kind. Further, our results are in agreement with those of Kaeoket et al [14] where addition of autologous or heterologous SP 50% (v/v) to extender yielded better viability as well as motility rates than in controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we found that treatment with either autologous or homologous SP resulted in higher viability rates as compared with control and, no detrimental effects when using the homologous kind. Further, our results are in agreement with those of Kaeoket et al [14] where addition of autologous or heterologous SP 50% (v/v) to extender yielded better viability as well as motility rates than in controls.…”
Section: Discussionsupporting
confidence: 93%
“…The protective effects of SP may be attributed to critical components such as antioxidant enzymes and other stabilizing proteins capable of modulating sperm function [12][13][14]. However, SP is removed prior cryopreservation to dilute the semen at a specific concentration in the extender.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and in the optimal ranges will have the most beneficial effect on sperm fertility at extended time intervals after thawing (Kaeoket et al. ).…”
Section: Quality Of the Cryopreserved Sperm Samplementioning
confidence: 99%
“…It has been shown that addition of the seminal plasma from the good freezer boars to the thawing extender improves in vitro sperm fertility (Hernandez et al 2007a). The type of seminal plasma and the concentration appears important as concentrations that are too high (>50%) could damage sperm whereas when too low (<15%) may have limited to no effect (Kirkwood et al 2008) and in the optimal ranges will have the most beneficial effect on sperm fertility at extended time intervals after thawing (Kaeoket et al 2011).…”
Section: Quality Of the Cryopreserved Sperm Samplementioning
confidence: 99%